Pediatric Research in Sports Medicine Research Interest Group Spine/Spondylolysis Clinical Practice SurveY. Issue 5 (31st May 2022) - Riederer, Mark F.; Achar, Suraj; McHorse, Kevin; MacDonald, James P.
Background: The Pediatric Research in Sports Medicine (PRiSM) society is a multi-disciplinary group of healthcare providers who provide clinical care to young athletes with a variety of conditions, including isthmic spondylolysis. It is thought that significant practice differences exist in the way providers diagnose, image, and treat this condition. Hypothesis/Purpose: The purpose of this study is to survey the members of PRiSM on clinical practice patterns in the diagnosis, imaging, and management of isthmic spondylolysis in young athletes. Methods: An electronic, thirty-three question REDCaps survey was distributed to the PRISM membership via email during the 2021 virtual annual meeting and one reminder was sent after the meeting. Responses were collected during a 6-week period. The survey collected information based upon the following: demographics, diagnosis, imaging, and management. Results: Ninety-eight surveys were completed. Most of the respondents were divided between orthopaedic surgeons, non-operative sports medicine physicians and physical therapists, approximately half of which are fellowship trained. Approximately 42% of respondents make the diagnosis based upon MRI results in addition to history, physical examination, and plain radiographs. Approximately 24% obtain oblique radiographs as part of their assessment. MRI is the most frequently used advanced imaging modality with nearly 90% of respondents using this. The use of rigid bracing varies widely among respondents, with 20.6% bracing regularly, 35.3% sometimes bracing, and 44.1% not using rigid braces at all. The use of non-rigid bracing is similarly varied with 17.6% prescribing this regularly, 44.1% sometimes, and 38.2% not using non-rigid bracing at all. There is variance as well with regards to initiation of physical therapy (PT): prescribing immediately (42.6%) versus prescribing a period to rest prior to PT (57.4%). When young athletes are returned to sport, 52.9% of respondents indicated that they would impose restrictions to activity and 47.1% would not. Conclusion: Although there are similarities in how the diagnosis of isthmic spondylolysis in young athletes is made by PRISM members, there is variability in management, especially the use of bracing, the timing of physical therapy, and return to sport restrictions. MRI is the most common advanced imaging modality being used to help with the diagnosis.